Inflammation-mediated vitamin K and vitamin D effects on vascular calcifications in people with HIV on active antiretroviral therapy. (1st April 2022) - Janus, Scott E.; Durieux, Jared C.; Hajjari, Jamal; Carneiro, Herman; McComsey, Grace A.
Abstract : Background: People with HIV (PWH) experience increased systemic inflammation and monocyte activation, leading to increased risk of cardiovascular events (death, stroke, and myocardial infarction) and higher coronary artery calcium scores (CACs). Vitamins D and K2 have significant anti-inflammatory effects; in addition, vitamin K2 is involved in preventing vascular calcifications in the general population. The roles of vitamins D and K in increased coronary calcifications in successfully treated PWH is less understood. Methods: We prospectively recruited 237 PWH on antiretroviral treatment (ART) and 67 healthy controls. CACs were derived from noncontrast chest computed tomography (CT) and levels of 25-hydroxyvitamin D (vitamin D) and inactive vitamin K-dependent dephosphorylated-uncarboxylated matrix Gla protein (dp-uc MGP, marker of vitamin K deficiency) were measured in plasma during a fasting state. The relationship between inflammation markers, dp-uc MGP, and vitamin D on CACs were estimated using zero-inflated negative binomial regression. Adjusted models included 25(OH)D, MGP, sex, race, age, and markers of inflammation or monocyte activation. Results: Overall, controls had lower median age (45.8 vs. 48.8; P  = 0.03), a larger proportion of female individuals (55.2 vs. 23.6%; P  < 0.0001), and nonwhite (33.8 vs. 70%; P  < 0.0001). Among PWH, less than 1% had detectable viral load and the median CD4 + cell count was 682 (IQR: 473.00–899.00). 62.17% of the participants had zero CACs and 51.32% were vitamin D-deficient (<20 ng/ml). There was no difference in detectable CACs ( P  = 0.19) or dp-uc MGP ( P  = 0.42) between PWH and controls. In adjusted models, PWH with nonzero CACs have three times greater expected CAC burden compared with controls. Every 1% increase in MGP (worse K status) decreases the probability of having CACs equal to zero by 21.33% ( P  = 0.01). Evidence suggests that the effects of 25(OH)D and MGP are inflammation-mediated, specifically through sVCAM, TNF-αRI, and TNF-αRII. Conclusion: Vitamin K deficiency is a modifiable preventive factor against coronary calcification in PWH. Further research should determine whether vitamin K supplementation would reduce systemic inflammation, vascular calcification, and risk of cardiovascular events in PWH.